Functional role of the human inferior colliculus in binaural hearing - Litovsky, Ruth Y.; Fligor, Brian J.; Tramo, Mark J. (Hearing research, 2002)
Psychophysical experiments were carried out in a rare case involving a 48 year old man (RJC) with a small traumatic hemorrhage of the right dorsal midbrain, including the inferior colliculus (IC). RJC had normal audiograms bilaterally, but there was a marked decrease in wave V amplitude on click-evoked brainstem auditory evoked potentials following left ear stimulation. RJC demonstrated a deficit in sound localization identification when the loudspeakers lay within the auditory hemifield contralateral to his IC lesion. Errors showed a consistent bias towards the hemifield ipsilateral to the lesion. Echo suppression was abnormally weak compared with that seen in control subjects, but only for sources contralateral to the lesion. Finally, speech intelligibility tests showed normal ability to benefit from spatial separation of target and competing speech sources. These results suggest that: (1) localizing sounds within a given hemifield relies on the integrity of the contralateral IC, (2) unilateral IC lesions give the illusion that sound sources in the ‘bad’ hemifield are displaced towards the ‘good’ hemifield, (3) the IC mediates aspects of echo suppression, and (4) lesion in the IC does not impede spatial release from masking in speech intelligibility, possibly due to that ability being more heavily mediated by cortical regions.